Pemberdayaan Masyarakat dalam Meningkatkan Aktivitas Fisik Mencegah Diabetes Melitus di RW 01 Tawangkulon, Kelurahan Tawangsari, Kecamatan Tawang, Kota Tasikmalaya - Sabila Syahadah Azizah; Shalwa Fitra Ramadhina; Aprilla Andini; Sausan Karimah; Sephia Zandra; Risma Nazmi Nuradila; Yolanda Priasti Irchamni; Andy Muharry (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Diabetes mellitus (DM) is a chronic disease characterized by abnormal blood sugar levels whose prevalence is increasing in Indonesia, including in Tasikmalaya City. Based on the Tasikmalaya City Health Office report in 2023, there were 11,782 DM patients, with 744 cases recorded in the Tawang Health Center working area. Tawangsari Village, namely RW 01, has health problems related to DM where people are less aware of the importance of implementing a healthy lifestyle, especially doing physical activity and limited posyandu services. The purpose of this “SEMANGGI” program is to increase community knowledge and awareness about DM prevention through education and joint gymnastics. The method used was participatory-based, involving health education through lectures, questions and answers, and the completion of pre-test and post-test to measure knowledge improvement. In addition, joint exercises designed to support a healthy lifestyle were conducted. Evaluation results showed a significant increase in community knowledge scores from an average of 2.65 in the pre-test to 4.45 in the post-test (p<0.001). This program demonstrates the effectiveness of participatory-based community empowerment in improving knowledge and promoting a healthy lifestyle to prevent DM. The sustainability of activities like this is needed to optimize its positive impact on public health.